Enhanced piezoelectric properties and temperature stability in KNN-based textured ceramics - Yan Lin; Ru Wang; Jiawei Qu; Shuo Gao; Yi Zhang; Junli Yan; Jigong Hao; Peng Li; Wei Li (Journal of Advanced Dielectrics, 2022)
Considering the advantages of high Curie temperature and environment-friendly nature of KNN piezoelectric ceramics, the limitation of weak piezoelectric response and their temperature sensitivity to applications is worth exploring. Herein, the <001> textured (1-[Formula: see text])(K[Formula: see text]Na[Formula: see text])(Nb[Formula: see text]Sb[Formula: see text])O3-[Formula: see text](Bi[Formula: see text]Na[Formula: see text])HfO3([Formula: see text] = 0.01−0.045) lead-free ceramics were synthesized by templated grain-growth method. The high piezoelectric performance (d[Formula: see text] of 474 pC/N and strain of 0.21%) and excellent temperature stability (unipolar strain maintained within 4.3% change between 30[Formula: see text]C and 165[Formula: see text]C) were simultaneously achieved in the textured KNNS-0.03BNH ceramics. The high piezoelectric performance can be attributed to the summation of the crystallographic anisotropy and phase structure contributions in <001> textured ceramics. The superior temperature stability of piezoelectric properties can be interpreted by the contribution of crystal anisotropy to piezoelectric properties reduces the effect of phase transition on piezoelectric properties deterioration. This study provides an effective strategy for simultaneously achieving high piezoelectric properties and superior temperature stability in KNN-based textured ceramics.